Disenchanting citizenship : Mexican migrants and the boundaries of belonging - Plascencia, Luis F. B. (Rutgers University Press, 2012)
Luis F.B. Plascencia's Disenchanting Citizenship explores two interrelated issues: U.S. citizenship and the Mexican migrants' position in the United States. Through an extensive and multifaceted collection of interviews, ethnographic fieldwork, ethno-historical research, and public policy analysis, Plascencia probes the ways in which citizenship discourses are understood and taken up by individuals. The book uncovers citizenship's root as a Janus-faced construct that encompasses a simultaneous process of inclusion and exclusion. This notion of citizenship is mapped on to t.
Keywords: Mexican Americans -- Ethnic identity.; Mexican Americans -- Civil rights.; Mexican Americans -- Social conditions.; Mexicans -- Migrations.; Citizenship -- United States.; Noncitizens -- United States.; United States -- Politics and government.; United States -- Ethnic relations.; United States -- Emigration and immigration -- Government policy.; Américains d'origine mexicaine -- Identité ethnique.; Américains d'origine mexicaine -- Droits.; Américains d'origine mexicaine -- Conditions sociales.; Mexicains -- Migrations.; Immigrants clandestins -- États-Unis.; États-Unis -- Politique et gouvernement.; États-Unis -- Relations interethniques.; États-Unis -- Émigration et immigration -- Politique gouvernementale.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Ethnic Studies -- General.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies.; Noncitizens; Citizenship; Emigration and immigration -- Government policy; Ethnic relations; Mexican Americans -- Civil rights; Mexican Americans -- Ethnic identity; Mexican Americans -- Social conditions; Politics and government; United States